2003
DOI: 10.1152/ajpregu.00010.2003
|View full text |Cite
|
Sign up to set email alerts
|

Urethral closure mechanisms under sneeze-induced stress condition in rats: a new animal model for evaluation of stress urinary incontinence

Abstract: The urethral closure mechanism under a stress condition induced by sneezing was investigated in urethane-anesthetized female rats. During sneezing, while the responses measured by microtip transducer catheters in the proximal and middle parts of the urethra increased, the response in the proximal urethra was almost negligible when the bladder response was subtracted from the urethral response or when the abdomen was opened. In contrast, the response in the middle urethra during sneezing was still observed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(177 citation statements)
references
References 33 publications
9
166
1
1
Order By: Relevance
“…Pelvic floor inhibition during voiding suggests similarities between rats and humans in the neural control of micturition. Some studies in rats have shown that levator ani denervation decreases urethral pressure and that neurectomized rats leak at sneeze (Conway et al 2005;Kamo et al 2003). However, we could not demonstrate a pelvic floor response during a LPP test and the LPP value did not decrease after levator ani nerve transection .…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Pelvic floor inhibition during voiding suggests similarities between rats and humans in the neural control of micturition. Some studies in rats have shown that levator ani denervation decreases urethral pressure and that neurectomized rats leak at sneeze (Conway et al 2005;Kamo et al 2003). However, we could not demonstrate a pelvic floor response during a LPP test and the LPP value did not decrease after levator ani nerve transection .…”
Section: Discussioncontrasting
confidence: 88%
“…Knowledge of the pathways of peripheral innervation is an important tool to study EUS function in preclinical studies (Cruz & Downie 2005;Jiang et al 2009aJiang et al , 2009bKamo & Hashimoto 2007;Kamo et al 2009;Kamo et al 2003;Kerns et al 2000;Lee et al 2003;Peng et al 2008aPeng et al , 2008b). Animal models have been used to estimate the damage to nerves during simulated childbirth and to test pharmacological and neuromodulation strategies to promote neuroregeneration and recovery of EUS function Cannon et al 2002;Jiang et al 2009aJiang et al , 2009bPeng et al 2008a;Streng et al 2001;Thor 2003;Thor et al 1989;Thor et al 2007;Vera & Nadelhaft 2001).…”
Section: Innervation Of the Eusmentioning
confidence: 99%
See 2 more Smart Citations
“…Kamo et al reported that opening the abdomen significantly decreases bladder pressure during a sneeze, indicating that the abdominal musculature contributes to the pressure increase during a sneeze. 8 The middle urethra generates a high pressure response to a sneeze that commences before the increase in abdominal pressure and is maintained relatively long after bladder pressure has returned to baseline, suggesting a sneeze induced active reflex muscle contraction to maintain continence activated directly by sneezing, rather than by afferent pathways from the bladder. By selectively transecting nerves Kamo et al determined that the reflex involved in maintaining continence during sneeze generation in urethane anesthetized female rats involves the pudendal nerve, and the nerves to the iliococcygeus and pubococcygeus muscles but not the visceral branches of the pelvic nerve or the hypogastric nerve.…”
Section: Assessment Of Sui In Animal Modelsmentioning
confidence: 98%